What is the solution of the equation (x – 5)2 + 3(x – 5) + 9 = 0? Use u substitution and the quadratic formula to solve.

What is the solution of the equation x 52 3x 5 9 0 Use u substitution and the quadratic formula to solve class=

Respuesta :

(x – 5)² + 3(x – 5) + 9 = 0

x
² - 10x + 25 + 3x - 15 + 9 = 0

x² - 7x - 16 = 0

[tex]x = \frac{7 + \sqrt{(-7)^2-4(1)(-16)} }{2} [/tex] or [tex]x = \frac{7 - \sqrt{(-7)^2-4(1)(-16)} }{2} [/tex] 

[tex] x = \frac{7 + 3i \sqrt{3} }{2} [/tex] or [tex] x = \frac{7 - 3i \sqrt{3} }{2} [/tex] 

(Answer B)

Answer: [tex]x=\frac{7\pm 3i\sqrt{3}}{2}[/tex]

Explanation:

Since, given quadratic function, [tex](x-5)^2 + 3(x-5) + 9 = 0[/tex] -----(1)

let us consider,[tex]x-5=p[/tex] -----(2)

Put this value in equation (1),

We get, [tex]p^2+3 p+9=0[/tex], which is also a quadratic equation.

Since, quadratic formula for finding the root of quadratic equation of type [tex]ax^2+bx+c=0[/tex] is,  [tex]x=\frac{-b\pm\sqrt{b^2-4ac}} {2a}[/tex]

Here, a=1, b=3  and c=9, so, [tex]p=\frac{-3\pm\sqrt{3^2-4\times1 \times9}} {2\times1}[/tex]

Thus,  [tex]p=\frac{-3\pm3\sqrt{-3}} {2}[/tex] ⇒ [tex]p=\frac{-3\pm3i\sqrt{3}} {2}[/tex]   (because √-1=i)

Now, from equation(2) [tex]x-5=\frac{-3\pm3i\sqrt{3}} {2}[/tex]

⇒[tex]x=\frac{-3\pm3i\sqrt{3}} {2}+5=\frac{7\pm 3i\sqrt{3}}{2}[/tex]

[tex]x=\frac{7\pm 3i\sqrt{3}}{2}[/tex]